Malawi Gender Assessment - World Bank (Washington, DC, 2022)
The government of Malawi has committed to addressing gender inequality and improving women’s wellbeing. The government has implemented multiple strategic development plans to guide policy creation and implementation. The current ongoing strategic plan is the Malawi Growth and Development Strategy (MDGS) III, which is aimed at alleviating poverty and fostering sustainable economic growth. In January 2021 the government of Malawi introduced the Malawi 2063 Vision, a strategic development plan which aims for low-middle income status by 2030.i To meet the goals set out in Malawi 2063, human capital development, private sector development, economic infrastructure, and environmental stability have been highlighted as critical drivers to be addressed. While the MDGS III and the Malawi 2063 Vision both include a focus on gender equality, this is largely done through a human capital and voice and agency lens, with considerably less focus on how closing gender gaps in the productive economic sectors can boost economic growth and poverty reduction. In the MDGS, gender is placed under ‘other development areas’ and grouped together with issues relating to youth, disability, and social welfare, with outcomes to be monitored including those focused on access to basic services, women’s roles in various levels of decision-making, and gender-responsive budgeting. In the Malawi 2063 Vision, gender is principally discussed under the human capital ‘enabler’ section.